Effect of air pollution on adult chronic diseases: Evidence from a quasi-natural experiment in China - Li, Yan; Xu, Sheng; Yin, Jinghua; Huang, Guan (Frontiers in Public Health, 2023)
We utilize a quasi-experiment derived from China's Huai River policy to investigate the effect of air pollution on adult chronic diseases. The policy led to higher pollution exposure in cities north of the river boundary because they received centralized coal-based heating supply from the government during winter, whereas cities in the south did not. By applying a geographic regression discontinuity design based on distance from the Huai River, we determine that a 10 μg/m3 increase in fine particulate matter (PM2.5) raises chronic diseases rates by 3.2% in adults, particularly cardiorespiratory system diseases. Furthermore, the same effects are observed on multiple chronic disease rates, but the rates are reduced to 1.3%. The effect of pollution exposure varies depending on age, gender, and urban/rural status. Our findings imply that reducing 10 μg/m3 of the average nationwide level of PM2.5 concentration will save 27.46 billion CNY (4.16 billion USD) in chronic disease costs.